Globalism, regionalism and nationalism: the dynamics of student mobility in higher education across the Taiwan Strait. Issue 4 (3rd July 2020) - Lo, William Yat Wai; Chan, Sheng-Ju
ABSTRACT: This paper aims to broaden the conceptual approaches to understanding the complexity of student mobility in higher education (HE) across the Taiwan Strait, thereby exemplifying a contradictory mix of collaboration and competition that involves interplay among the various forces associated with global, regional and national settings. To achieve this goal, the paper provides an abstraction of 'trichotomisation', which explains the significance of the concepts of globalism, regionalism and nationalism in understanding cross-Strait student mobility, and thus shows its threefold nature. Specifically, it considers the intensification of cross-Strait student mobility in HE and the counter-reaction as a manifestation of globalism, a form of regionalism, and an expression of nationalism.